Antipopulistas reaccionarios en el espacio público digital - Kessler, Gabriel; Vommaro, Gabriel; Paladino, Martín (El Colegio de México, 2022)
Conservative influencers are emerging from the contemporary Latin American reactionary right and contributing to its reconstitution. We describe their profiles using a typology based on the identification of their organizational supports and the scope of their agenda.Although we find conservative (“cultural war” against “gender ideology”) and libertarian (anti-statism) agendas, both converge on anti-populism. We identify their intervention strategies in the digital public space and the type of followers. We combine a supply-side approach –disputes within the right and in the public sphere in general –and a demand-side approach– the mobilization of conservative followers. We use data from a quali-quantitative study on the off-line and on-line interventions of four influencers from four Latin American countries.